Oxidative Addition of Diorgano Disulfides to Distannyne [{2, 6‐(Me2NCH2)2C6H3}Sn]2. Issue 2 (20th November 2013) - Bouška, Marek; Novák, Miroslav; Dostál, Libor; Růžička, Aleš; Mikysek, Tomáš; Metelka, Radovan; Jambor, Roman
Abstract: Reactivity of [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn]2 (1 ) towards functionalized diorganodisulfides R2 S2 as oxidizing agents was studied. The reactions provided organotin(II) thio derivatives {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(S2 CNMe2 ) (2 ), {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn (SC6 H4 ‐2‐NH2 ) (3 ) and {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC5 H4 N) (4 ). The 119 Sn NMR spectroscopic data of2 –4 suggest different electronic saturation of the tin(II) atoms in2 –4, which caused redox stability of2 and easy oxidation of3 and4 . The treatment of the latter compounds with diorgano disulfides R2 S2 yielded organotin(IV) thio derivatives {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC6 H4 ‐2‐NH2 )3 (5 ) and {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC5 H4 N)3 (6 ). In addition, oxidation of3 and4 with the radical TEMPO (2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl) provided organotin(IV) hydroxide [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC6 H4 ‐2‐NH)(μ‐OH)]2 (7 ) and organotin(IV) oxide [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC5 H4 N)(μ‐O)]3 (8 ). All prepared compounds2 –8 were characterized by using multinuclear NMR spectroscopy, and the molecular structures of2, 4, 7 and8 were determined by using X‐ray diffraction. Compounds2 –4 were also characterized by cyclic voltammetry. Abstract : Oxidation reactions of [{2, 6‐(Me2 NCH2 )2 C6 H3 }Sn]2 by diorganodisulfides R2 S2 were studied. The reactions provided organotin(II) thio derivatives {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(S2 CNMe2 ), {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC6 H4 ‐2‐NH2 ), and {2, 6‐(Me2 NCH2 )2 C6 H3 }Sn(SC5 H4 N). Their 119 Sn NMR spectroscopic data suggested different electronic saturation of the tin(II) atoms.